Quantifying an Overlooked Deciduous‐Needleleaf Carbon Sink at the Southern Margin of the Central‐Siberian Permafrost Zone. Issue 3 (20th March 2023) - Liu, Jialin; Cheng, Fangyan; Commane, Róisín; Zhu, Yi; Ji, Weiwen; Man, Xiuling; Guan, ChengHe; Munger, J. William
Abstract: With over 700 million km 2 Siberia is the largest expanse of the northern boreal forest—deciduous‐needleleaf larch. Temperatures are increasing across this region, but the consequences to carbon balances are not well understood for larch forests. We present flux measurements from a larch forest near the southern edge of Central‐Siberia where permafrost degradation and ecosystem shifts are already observed. Results indicate net carbon exchanges are influenced by the seasonality of permafrost active layers, temperature and humidity, and soil water availability. During periods when surface soils are fully thawed, larch forest is a significant carbon sink. During the spring‐thaw and fall‐freeze transition, there is a weak signal of carbon uptake at mid‐day. Net carbon exchanges are near‐zero when the soil is fully frozen from the surface down to the permafrost. We fit an empirical ecosystem functional model to quantify the dependence of larch‐forest carbon balance on climatic drivers. The model provides a basis for ecosystem carbon budgets over time and space. Larch differs from boreal evergreens by having higher maximum productivity and lower respiration, leading to an increased carbon sink. Comparison to previous measurements from another northern larch site suggests climate change will result in an increased forest carbon sink if the southern larch subtype replaces the northern subtype. Observations of carbon fluxes in Siberian larch are still too sparse to adequately determine age dependence, inter‐annual variability, and spatial heterogeneity though they suggest that boreal larch accounts for a larger fraction of global carbon uptake than has been previously recognized. Plain Language Summary: Cold, wet soils in boreal forests contain a large amount of carbon. However, warmer temperatures coupled with changes in hydrology could release stored carbon and accelerate its decomposition. The boreal spruce and pine forests in North America and Fennoscandia have been studied extensively, but observations in the Siberian larch forests are limited. Because larch shed their needles in winter their response to changing temperature and moisture may differ from expectations based on evergreen conifers. Our work focuses on a larch forest in northern China that is at the southern edge of the Central‐Siberian biome where eco‐environmental changes are starting to occur. By studying how the annual growth and carbon balance in this forest respond to variations in weather we will be better able to predict significant changes in the structure and function of the larch ecosystem that could undermine regional ecosystem stability. Larch forest functions differently from evergreen needle‐leaf forests and provides the larger carbon sink than had been previously recognized. Key Points: Seasonality in permafrost active layer and environmental temperature‐humidity dynamics closely regulate boreal larch' carbon cycle Ecosystem functional traits in deciduous larch are distinct from other boreal needleleaf evergreens By inadequately accounting for boreal larch's carbon sink, the estimates of global forest carbon budgets will be biased low